Laboratory Examination in Hepatocelullar Carcinoma - Debie Anggraini (Health and Medical Journal, 2019)
Hepatocellular carcinoma (HCC) is a malignant tumor originating from hepatocyte cells including primary malignant tumors of the epithelial liver. Hepatocellular carcinoma is the fifth most malignant in the world and the third largest cause of death of all malignancies. Diagnosis of HCC is obtained from the patient's history, examination of the patient, by imaging (ultrasonography, MRI or CT scan) and an increase in serum tumor biomarkers of alpha feto protein (AFP) (> 400 ng mL). Early diagnosis is important to increase the patient's life expectancy and only 30-40% of patients are diagnosed at an early stage. Biomarkers in HCC not only help in diagnosing but also predict prognosis or recurrence and in choosing therapy. The stability of miRNA in blood circulation makes miRNA an ideal candidate for use in the diagnosis and treatment of cancer. Objective: to briefly review all current information about HCC. Conclusion: HCC diagnosis is obtained from the patient's history, physical examination, imaging (ultrasonic, MRI or CT scan that shows the presence of a typical liver mass for HCC) and an increase in AFP serum (> 400 ng / mL). Biomarker examination and evaluation is still very limited, one of which is the examination of MicroRNAs